The effectiveness of a leg-kicking training program on performance and physiological measures of competitive swimmers - Konstantaki, M.; Winter, E. M. (International Journal of Sports Science and Coaching, 2007)
This study investigated the adaptations in leg muscle metabolism of swimmers following a six-week, leg-kicking swimming training program. Fifteen male competitive swimmers were randomly assigned to an experimental group (E; n=8) and a control group (C; n=7). E swimmers performed normal leg-kicking training three times per week, whereas C swimmers performed reduced leg-kicking training (20% and 4% of weekly training distance, respectively). Before and after the training program, all swimmers performed a 200 m leg-kicking and a 400 m full-stroke freestyle time trial and a dry-land exercise test during which peak oxygen uptake, oxygen uptake at 60 W and exercise intensity at ventilatory threshold were measured. After training, there were improvements in leg-kicking time in 200 m (s; -6.0 ± 2.0%, p = 0.044), oxygen uptake at 60 Watts (L·min-1; -20.4 ± 3.0%, p = 0.035) and exercise intensity at ventilatory threshold (Watts; +28.0 ± 5.0%, p = 0.023) in E swimmers, whereas time in 400 m and peak oxygen uptake remained unchanged (p > 0.05). There were no changes in any of the measures for C swimmers (P > 0.05). These results suggest that normal leg-kicking swimming training positively affects the conditioning of the legs, but does not improve aerobic power during the dry-land, leg-kicking exercise test or middle-distance, full-stroke, swimming performance.